2019
DOI: 10.1001/jamanetworkopen.2019.0047
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Analysis of Bariatric Surgery for Patients With Nonalcoholic Steatohepatitis Cirrhosis

Abstract: Key Points Question Is bariatric surgery cost-effective in patients with nonalcoholic steatohepatitis and compensated cirrhosis? Findings In this simulation model study, laparoscopic sleeve gastrectomy had an incremental cost-effectiveness ratio of $66 119 per quality-adjusted life-year in overweight patients, $18 716 per quality-adjusted life-year in patients with mild obesity, $10 274 per quality-adjusted life-year in patients with moderate obesity, and $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 58 publications
0
32
0
1
Order By: Relevance
“…A further two articles were identified through supplementary searches of grey literature. As such, a total of 19 articles [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (capturing 16 different models) were included in the review; summary details of identified studies are shown in Table 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further two articles were identified through supplementary searches of grey literature. As such, a total of 19 articles [11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (capturing 16 different models) were included in the review; summary details of identified studies are shown in Table 1.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 13 articles assessed health economic outcomes associated with different screening or diagnostic strategies [16,[18][19][20][21][26][27][28][29][30][31][32][33]; five assessed outcomes with different treatments, including lifestyle intervention, pioglitazone, vitamin E and obeticholic acid as well as bariatric surgery for overweight/obese patients with NASH [17,[22][23][24][25]. The remaining article examined the overall clinical and economic burden of disease and as such was a non-comparative study [11].…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic characteristics and clinical data are summarized in Table 1. The mean age was 57 ± 13 years, 54% were men, more than 63% achieved higher than a high school diploma, 49% were Child A, 37% were Child B, 14% were Child C, and the median MELD-Na score was 12 (interquartile range [IQR], [8][9][10][11][12][13][14][15][16][17][18]. NAFLD/nonalcoholic steatoheptitis (NASH) (30%) was the most common etiology followed by alcohol (26%) and aviremic/cured-hepatitis C virus (14%).…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…The epidemiology of cirrhosis has shifted, now characterized by aging persons with nonalcoholic fatty liver disease (NAFLD), alcoholrelated disease, or treated hepatitis C. (7) Cost-effectiveness analyses depend on generalizable utilities but continue to use extremely dated values that are often more than 20 years old and derived from patients with viremic hepatitis C, few of whom had decompensated cirrhosis and few of which capture the contribution of specific cirrhosis symptoms. (8)(9)(10)(11) Updated heath-state utilities are therefore needed in order to execute meaningful cost-effectiveness studies that represent contemporary patients. Herein, we prospectively evaluated health-state utilities in a large cohort of patients with cirrhosis.…”
mentioning
confidence: 99%